A randomised observational study of individualised variations in the start position of the closed-kinetic chain upper extremity stability test. (January 2020) - Callaway, Andrew; Peck, Joshua; Ellis, Shelley; Williams, Jonathan
Abstract: Objectives: To assess the reliability, precision and differences between scores produced using the standard 36″ start position and 3 modified start positions of the Closed Kinetic Chain Upper Extremity Stability Test (CKCUEST), towards normalisation to the individual. Design: RCT of 4 conditions. Setting: Clinical. Participants: Thirty-four asymptomatic individuals. Main outcome measures: Using an RCT method, variations in CKCUEST starting hand position were tested using hand spacing at standard 36″, 50% height, bi-acromial distance, and bi-acromial distance with reach to 36″. The average number of touches over 3 × 15 s maximal efforts were used to assess the intra-variation reliability, minimum detectable change (MDC) and differences to the standard 36″ start position. Results: The most reliable variation was the 50% height (ICC: 0.93) and with the smallest MDC (14%). 36″ results were second-most reliable (ICC: 0.90), with a low MDC (19%). Significant differences were found between bi-acromial and 50% height to the 36″ standard setup. Conclusions: A setup position where the hand separation is 50% of the individual's height offers excellent repeated measures reliability and the smallest MDC, suggesting it is the most sensitive to change and is a recommendation to clinicians. Conversion calculations between start variations are presented. Highlights: Variations in hand spacings for CKCUEST were examined. Normalising hand spacing to the individual's anthropometrics is reliable. 50% height hand placement was shown to be the most reliable and sensitive to change (MDC). Variations produced significantly different mean touches when compared to the standard 36″ setup. The validation of the test in different start positions should be examined.